Full-band UV shielding and highly daylight luminescent silane-functionalized graphene quantum dot nanofluids and their arbitrary polymerized hybrid gel glasses. Issue 41 (10th October 2016) - Xie, Zheng; Du, Qingqing; Wu, Yongzhong; Hao, Xiaopeng; Liu, Chunyan
Abstract : A facile and efficient approach for the preparation of silane-functionalized graphene quantum dot (SiGQD) nanofluids is described. Abstract : A facile and efficient approach for the preparation of silane-functionalized graphene quantum dot (SiGQD) nanofluids is described. The functionalized SiGQDs are self- and co-polymerized with silane to easily obtain the arbitrary concentration (0–100%) of SiGQD doped organically modified silicate gel glasses with good processability. The glasses feature arbitrary concentration doping, transparency, homogeneity, various solid structures, luminescence and full-UV shielding capability and are thus suitable for the preparation of bulk hybrid nanocomposites. The SiGQDs with functional groups attached to the surface are strongly photoluminescent both in solution (quantum yield = 82%) and in the solid state (96%). The trace amounts of UV light in daylight could excite these materials and could be observed by the naked eye. The resultant SiGQDs and their gel glasses can absorb and convert UV light into blue light, which can be effectively modulated by the arbitrary concentration of the SiGQDs. These non-toxic, low cost, heavy metal-free, and eco-friendly SiGQDs and their corresponding gel glass systems are promising candidates for high performance UV filters as well as optical materials and devices.